2002
DOI: 10.1016/s1470-0328(02)01314-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measurement of peak systolic velocity in the fetal middle cerebral artery for monitoring pregnancies complicated by red cell alloimmunisation: a prospective multicentre trial with intention-to-treat

Abstract: Objective To evaluate the utilisation measurements of peak systolic velocities in the middle cerebral artery combined with B-mode ultrasound imaging to predict anaemia in an unselected population of pregnancies complicated by alloimmune antibodies known to cause immunological hydrops. Design Prospective study on an intention-to-treat basis.Setting Multicentre study in five large tertiary referral centres.Population One hundred twenty-five fetuses with maternal alloantibodies known to cause immunological hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…5 The MCA-PSV may be falsely increased when the measurement is performed during a period of rest that follows a period of fetal activity, or late in gestation in accordance with fetal heart rate accelerations. 7 A third prospective, international trial performed by the The Decision Aids for Mode of Next Delivery study group supported the replacement of invasive testing (amniocentesis) with MCA-PSV Doppler studies, confirming the sensitivity of the original study. 6 In a study of the Collaborative Group for Doppler Assessment of the Blood Velocity in Anemic Fetuses, 3 MCA-PSV values were collected from a group of at-risk fetuses undergoing cordocentesis.…”
Section: The Techniquementioning
confidence: 73%
See 1 more Smart Citation
“…5 The MCA-PSV may be falsely increased when the measurement is performed during a period of rest that follows a period of fetal activity, or late in gestation in accordance with fetal heart rate accelerations. 7 A third prospective, international trial performed by the The Decision Aids for Mode of Next Delivery study group supported the replacement of invasive testing (amniocentesis) with MCA-PSV Doppler studies, confirming the sensitivity of the original study. 6 In a study of the Collaborative Group for Doppler Assessment of the Blood Velocity in Anemic Fetuses, 3 MCA-PSV values were collected from a group of at-risk fetuses undergoing cordocentesis.…”
Section: The Techniquementioning
confidence: 73%
“…7 A third prospective, international trial performed by the The Decision Aids for Mode of Next Delivery study group supported the replacement of invasive testing (amniocentesis) with MCA-PSV Doppler studies, confirming the sensitivity of the original study. 3,7 The noninvasive nature of MCA-PSV inherently avoids risks such as premature rupture of the membranes, infection, worsening alloimmunization, and fetal loss associated with amniocentesis and cordocentesis. 3,4 In addition, the MCA-PSV more accurately reflects hemoglobin concentrations in severe anemia up to a hemoglobin level of 1 to 3 g/dL, at which point blood velocity no longer increases.…”
Section: The Techniquementioning
confidence: 73%
“…In the retrospective analysis of Mari et al4, a MCA-PSV of greater than 1.5 MOM was associated with a false positive rate of 10% for the detection of moderate to severe anemia. Zimmerman et al10 undertook a prospective multi-center trial and reported a similar false positive rate of 13%. Finally, Oepkes and coworkers11 noted a slightly higher false positivity of 18% for the detection of severe fetal anemia when the MCA-PSV was greater than 1.5 MOM.…”
Section: Commentmentioning
confidence: 94%
“…Normative data have been published by the group of Mari et al (Fig. 51 A recent comprehensive multicentre study by Oepkes et al in which MCA PSV and amniocentesis were performed prior to cordocentesis reported that MCA PSV is superior to amniocentesis in detecting fetal anaemia in red cell alloimmunization cases and can be safely used for the timing of cordocentesis and/or intrauterine transfusion. In this study, all fetuses with moderate or severe anaemia had peak systolic values above 1.5 times the median.…”
Section: Mca In Fetal Anaemiamentioning
confidence: 99%